Effect of Different Friction Stir Spot Welding Techniques on the Mechanical Properties and Microstructure of Aluminum AA2024-T3 - Mahdi, Akeel Z.; Amin, Samir A.; Bakhy, Sadeq H. (Al-Nahrain Journal for Engineering Sciences, 2019)
This paper presents a comparison of using different techniques for stir spot welding of Aluminum 2024-T3, which are refill friction stir spot welding (RFSSW), edited (RFSSW-pin) and conventional friction stir spot welding (FSSW), depending on the obtained tensile shear strength property. Specimens were prepared from AA2024-T3 sheet for chemical analysis and mechanical tests. Workpieces were stir spot welded utilizing the above mentioned techniques at four rotational speeds (2000, 2500, 3000 and 4000 rpm) using tool pin diameters (5 and 7 mm) for conducting the tensile shear tests. The microhardness along the cross section of the welded specimens was conducted at the best conditions as well as the microstructure examination. The comparison results revealed that at the rotational speeds (2000 and 4000 rpm) in both cases of tool pin (5 and 7 mm), the ultimate tensile shear force was slightly higher than that for other speeds. However, the ultimate tensile shear force was found higher at 3000 rpm speed with a tool pin 7 mm. The microhardness results manifested a W-shape at the best conditions. Finally, the microstructure examination depicted the morphology of the main zones of the weld joint.